Release of Selected Non-Intentionally Added Substances (NIAS) from PET Food Contact Materials: A New Online SPE-UHPLC-MS/MS Multiresidue Method - Riccardo Aigotti; Nicola Giannone; Alberto Asteggiano; Enrica Mecarelli; Federica Dal Bello; Claudio Medana (Separations, 2022)
Food contact materials (FCMs) are an underestimated source of food chemical contaminants and a potentially relevant route of human exposure to chemicals that are harmful to the endocrine system. Foods and water are the main sources of exposure due to contact with the packaging materials, often of polymeric nature. European Regulation 10/2011 requires migration tests on FCMs and foodstuffs to evaluate the presence of listed substances (authorized monomers and additives) and non-intentionally added substances (NIAS) not listed in the regulation and not subjected to restrictions. The tests are required to ensure the compliance of packaging materials for the contained foods. NIAS are a heterogeneous group of substances classified with a potential estrogenic or androgenic activity. Subsequently, the evaluation of the presence of these molecules in foods and water is significant. Here we present an online SPE/UHPLC-tandem MS method to quantify trace levels of NIAS in food simulants (A: aqueous 3% acetic acid; B: aqueous 20% ethanol) contained in PET preformed bottles. The use of online SPE reduces systemic errors thanks to the automation of the technique. For the developed analytical method, we evaluate the limit of detection (LOD), the limit of quantitation (LOQ), selectivity, RSD% and BIAS% for LLOQ for a total of twelve NIAS, including monomers, antioxidants, UV-filters and additives. LOD ranged between 0.002 µg/L for bisphenol S and 13.6 µg/L for 2,6-di-tert-butyl-4-methylphenol (BHT). LOQs are comprised between 0.01 µg/L for bisphenol S and 42.2 µg/L for BHT. The online-SPE/UHPLC-tandem MS method is applied to the food simulants contained in several types of PET packaging materials to evaluate the migration of the selected NIAS. The results show the presence (µg/L) of NIAS in the tested samples, underlining the need for a new regulation for these potentially toxic molecules.